Ruling Ireland, 1685-1742 : politics, politicians and parties - Hayton, David, 1949- (Irish historical monographs series., 2004)
In a series of studies, David Hayton offers a comprehensive account of the government of Ireland during the period of transformation from 'New English' colonialism to Anglo-Irish 'patriotism', providing a chronological survey of the development of English policy towards Ireland and an account of the changing political structure of Ireland; particular attention is paid to the emergence of an English-style party system under Queen Anne.